Epistemological beliefs in relation to the Content, teaching and learning of mathematics teachers: Creencias epistemológicas en relación al contenido, enseñanza y aprendizaje de profesores de matemáticas - Uzuriaga López, Vivian Libeth (Scientia et Technica, 2021)
One result of the research is the paper "integral intervention of mathematics' teaching and learning processes" developed in a public university in Colombia, Latin America. The analysis of the epistemological beliefs of a group of academics from the Mathematics Department, who teach subjects to engineer and technology students is presented. We performed descriptive and quantitative cohort research. The objective was to identify the beliefs regarding mathematics' content, learning, and teaching. The 56 participants were included from a voluntary sample, in which the majority were engineers. A questionnaire adapted from Vizcaíno, with a specific domain of mathematical beliefs, approached from the multidimensional model de Schommer was used as a measuring instrument. The results showed that, in general, the teachers' system beliefs are naive or simple and in some specific topics sophisticated. It was observed a percentage of teachers who didn't assume a precise position in their beliefs when responding neutrally to the questionnaire, which could be interpreted as a lack of reflection on their teaching practice, which revealed the need to generate discussion spaces for promoting reflective practices that improve the mathematics' learning. Likewise, the need for training in mathematics' history, epistemological knowledge, and didactics was evidenced, which promotes better mathematics teaching practices.